FACTORS FOR SELECTING CHILDBIRTH ASSISTANT IN SP 2 HILL TELUK MUNDUR PELALAWAN DISTRICT (Proceedings OPTIMAL, 2024)
In Indonesia, developing mother and child health is of utmost importance for the advancement of health. The reason for this is that throughout pregnancy, labor, and the postpartum period, mothers and children are particularly vulnerable populations. Consequently, evaluating maternal health issues is crucial. An indication of how well maternal health initiatives are working is the Maternal Mortality Rate (MMR) metric. There are several factors to consider while selecting a birth attendant. The emotional connection is one of the reasons why someone would rather give birth to a dukun beranak than a village midwife. Through comfort and cultural commonalities, the tight contact between the shaman and the patient fosters a strong sense of togetherness that can provide solace to moms who have problems during childbirth. This study aims to determine the factors that influence the choice of birth attendant by mothers giving birth. The purpose of cross-sectional, quantitative study is to identify the variables that affect laboring women' choice of birth attendants. Using random sampling, the study's sample consisted of 47 laboring mothers. The investigation was conducted at Pelalawan Village's SP II Teluk Mundur. Factors in selecting a birth assistant carried out by mothers giving birth at SP II Teluk Mundur, Pelalawan Sub-district. Out of 5 factors, there are related factors, namely education, knowledge, attitude and culture factors and there is 1 unrelated factor, namely the economic status factor.